Analisis Penggunaan Smartphone Wisatawan Muslim Gen-Z: Sebuah Penelitian Interpretative Phenomenology Analysis - Kurnia, Agus; Sugiyanto, Catur; Purnomo, Boyke Rudy; Kusworo, Hendrie Adji (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
Halal tourism is becoming increasingly popular among Muslim tourists interested in international travel. Internationally, Muslim tourists who travel a lot are young tourists, on average 24 years old, and have a good education. Statistically, Generation Z dominates travel in Indonesia. Generation Z is a generation born between 1993-2012 (30-11 years old) and known as